2016
DOI: 10.15226/2381-2915/2/2/00114
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude & Practice Study on Screening of Cervical Cancer Among Women Visiting A Tertiary Care Center

Abstract: Context: Cervical cancer is the most common cancer among women in India and ranked fourth worldwide. The long precancerous stage of cervical cancer provides a window period for screening and early detection. Evaluation of knowledge and attitude towards them is important for effective implementation of screening programmes especially in a low resource setting. No such studies have been conducted in this region where estimated incidence rate of cervical cancer is quite significant. There is no provision availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In contrast to the results of the present study, Pattupara et al reported from Uttrakand that 93% had no knowledge about cancer cervix. 6 Among the studies conducted abroad, Touch et al reported 74%, Shrestha et al reported 65.7% and Tran NT et al reported more than 60% having heard of the disease in Combodia, Nepal and Korea respectively. [7][8][9] In the current study , friends and relatives followed by media were the main information sources for the respondents and these results are in agreement with those reported by Narayana et al and Abdullahi et al 5,10 More than 80% of the respondents were aware that cervical cancer was preventable and about the availability of screening test for the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the results of the present study, Pattupara et al reported from Uttrakand that 93% had no knowledge about cancer cervix. 6 Among the studies conducted abroad, Touch et al reported 74%, Shrestha et al reported 65.7% and Tran NT et al reported more than 60% having heard of the disease in Combodia, Nepal and Korea respectively. [7][8][9] In the current study , friends and relatives followed by media were the main information sources for the respondents and these results are in agreement with those reported by Narayana et al and Abdullahi et al 5,10 More than 80% of the respondents were aware that cervical cancer was preventable and about the availability of screening test for the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these studies, Narayana et al reported that more than half of population of women were aware of symptoms, risk factors and preventive measures for cervical cancer. 5,6 Similar findings were also reported from North Uganda by Mukana et al 11 The most important risk factor mentioned by respondents in the present study was multiple sex partners which was in consonance with that reported by Bansal et al 12 Bleeding from intercourse was the commonly mentioned symptoms in the present study whereas intermenstrual bleeding was commonly reported by Bansal et al 12 Attitude among half of the respondents were positive on parameters like cervical cancer being not transmitted from one patient to another and screening being a harmless procedure for the client. However, in contrast, most of the respondents showed positive attitude towards cervical cancer in the study conducted by Narayan et al 5 More than three fourth were willing to utilize free screening for cancer cervix if offered.…”
Section: Discussionmentioning
confidence: 99%
“…6 Poor awareness level was found in another study by Archana et al conducted at AIIMS, Rishikesh on women attending outpatient departments in which 74% of respondents had never heard of cervical cancer. 7 In this study, 82% of the patients were symptomatic since more than five years but took no medical care because of lack of awareness about the disease.…”
Section: Discussionmentioning
confidence: 77%
“…Studies included in review concluded that in India women still lack in appropriate knowledge and attitude toward Cervical Cancer and screening techniques due to low literacy rate. The articles reviewed showed that age, 9,10,12,18 education 3,[13][14][15][16][17][18][19][20] and per capita income 12,17,18 were significant factors independently associated with adequacy of knowledge, attitude, and practice of Cervical Cancer screening. (Table 1) Among 19 studies reviewed, 18 3,[9][10][11][12][13][15][16][17][18][19][20][21][22][23][24][25][26] reported the knowledge on Cervical Cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Among 19 studies reviewed, 18 3,9 -13,15 -26 reported the knowledge on Cervical Cancer. The overall knowledge on Cervical Cancer among women was 40.22%.…”
Section: Resultsmentioning
confidence: 99%